Associations between Body Mass Index and Park Proximity, Size, Cleanliness, and Recreational Facilities. Issue 4 (March 2013) - Rundle, Andrew; Quinn, James; Lovasi, Gina; Bader, Michael D. M.; Yousefzadeh, Paulette; Weiss, Christopher; Neckerman, Kathryn
Purpose: To determine whether body mass index (BMI) is associated with proximity to neighborhood parks, the size of the parks, their cleanliness, and the availability of recreational facilities in the parks. Design. Cross-sectional. Setting: New York City. Subjects: Adults (13, 102) were recruited from 2000 to 2002 (median age 45 years, 36% male). Measures: Anthropometric and sociodemographic data from study subjects were linked to Department of Parks & Recreation data on park space, cleanliness, and facilities. Neighborhood-level sociodemographic and park proximity metrics were created for half-mile–radius circular buffers around each subject's residence. Proximity to park space was measured as the proportion of the subject's neighborhood buffer area that was total park space, large park space (a park > 6 acres) and small park space (a park #6 acres). Analysis: Hierarchical linear models were used to determine whether neighborhood park metrics were associated with BMI. Results: Higher proximity to large park space was significantly associated with lower BMI (beta = −1.69, 95% confidence interval = −2.76, –.63). Across the population distribution of proximity to large park space, compared to subjects living in neighborhoods at the 10th percentile of the distribution, the covariate-adjusted average BMI was estimated to be .35 kg/m 2 lower for those living in neighborhoods at the 90th percentile. The proportion of neighborhood area that was small park space was not associated with BMI, nor was park cleanliness or the availability of recreational facilities. Conclusion: Neighborhood proximity to large park spaces is modestly associated with lower BMI in a diverse urban population.